YAJUJ DAN MAJUJ DALAM TAFSIR AL-AZHAR (PENDEKATAN HERMENEUTIKA EMILIO BETTI) - Supomo dan M. Riyan Hidayat (Program Studi Ilmu Al-Qur'an dan Tafsir, Institut Agama Islam Negeri (IAIN) Palu, 2021)
The coming of the Day of Judgment is rumored to be the emergence of Gog and Magog is still a hot debate, various ways have been done, including Hamka who ijtihad in explaining it. This paper uses a literature review using descriptive-analytical methods assisted by Emilio Betti's Hermeneutics theory as an umbrella in this study. Gog and Magog understood by Hamka are very different from the interpretations made by other commentators whose interpretation when viewed from Betti's theory is very dynamic.